Study of Effect of Concentrated Cryoprotective Medium on Survival and Fertilizing Ability of Frozen-Thawed Bovine Sperm - Pavlenko, B. M. (Problems of Cryobiology and Cryomedicine, 2007)
The research results on optimization of cryoprotective and sanitary indices of yolk-containing medium were presented. It has been established that concentrating of yolk-containing medium and a concentrate warming at 75Â°C for 30 min provided sterility and stability of cryoprotective properties at its storage at room temperature conditions for 12 months as minimum.